Increasing the molecular weight of conjugated polyelectrolytes improves the electrochemical stability of their pseudocapacitor gels. Issue 40 (28th September 2022) - Vázquez, Ricardo Javier; Quek, Glenn; McCuskey, Samantha R.; Llanes, Luana; Kundukad, Binu; Wang, Xuehang; Bazan, Guillermo C.
Abstract : Increasing the molecular weight of conjugated polyelectrolytes leads to improvements in capacitance and cycling stability, to the point where it is possible to retain 76% of the original performance after 100 000 charge–discharge cycles. Abstract : Conjugated polyelectrolyte (CPE) hydrogels synergize the electrical properties of redox-active polymers with the physical properties of hydrogels. Of particular relevance is their implementation as pseudocapacitors due to their high ionic conductivity, strong ionic–electronic coupling, and large electroactive surface area. To date, efforts to improve the cycling stability of such hydrogels are predominated by the use of additives – optimization of the CPE's intrinsic properties remains underexplored. Herein, the systematic increase in the molecular weight (MW) of a self-doped CPE, namely CPE-K, has been demonstrated as an effective strategy to enhance the cycling stability of the resulting hydrogel. At high MW, mechanically stronger hydrogels were obtained with a specific capacitance as high as 88 ± 4 F g −1 at 0.25 A g −1 and a cycling stability of 76% capacitance retention after 100 000 cycles at 2.5 A g −1 . Furthermore, this strategy yields a wider working pseudocapacitive window, less internal resistance, and higher ionic conductivity within the 3D conductive network. We attribute the enhanced electrochemical performance to stronger inter-chain contacts for optimal morphological organization, as revealed by rheological measurements, resulting in stress-tolerant hydrogels with a higher degree of percolation within a 3D conductive network. These results position CPE-K hydrogels as a state-of-the-art organic material for long-term pseudocapacitive technologies and potentially for the next generation of multi-functional pseudocapacitive devices that go beyond high energy density and power density.